Finite element analysis with error estimators an introduction to the FEM and adaptive error analysis for engineering students - Akin, J. E. (Elsevier/Butterworth-Heinemann, 2005)
This key text is written for senior undergraduate and graduate engineering students. It delivers a complete introduction to finite element methods and to automatic adaptation (error estimation) that will enable students to understand and use FEA as a true engineering tool. It has been specifically developed to be accessible to non-mathematics students and provides the only complete text for FEA with error estimators for non-mathematicians. Error estimation is taught on nearly half of all FEM courses for engineers at senior undergraduate and postgraduate level; no other existing textbook for this market covers this topic. *The only introductory FEA text with error estimation for students of engineering, scientific computing and applied mathematics *Includes source code for creating and proving FEA error estimators *Complete with homework exercises and supporting website with instructor's solutions manual.